Synthesis, Crystal Structure, Spectroscopic Characterization and Theoretical Calculations of (Z)-N-(naphthalen-2-yl)-1-(5-nitrothiophen-2-yl)methanimine - Özdemir Tarı, G.Ö.; Aģar, E. (Elsevier B.V., 2017)
The newly synthesized Schiff base compound, (Z)-N-(naphthalen-2-yl)-1-(5-nitrothiophen-2-yl)methanimine, C15H10N2O2S, was characterized by IR, UV–Vis and X-ray diffraction technique. All of the theoretical calculations have been calculated at the LSDA, BVP86, B3LYP and B3PW91 levels of the density functional method (DFT) with the 6–311++G(d,p) basis set by Gaussian software. UV–Visible absorption spectra of the title compound dissolved in ethanol were recorded and computed using the time dependent density functional theory (TD-DFT). The harmonic vibrational frequencies of the title compound were calculated using the same methods. So as to determine most favorable conformation as theoretically, molecular energy profile of the title compound were obtained as a function of the selected torsion angle by steps of 10° in the range of −180° to +180° rotation around the bond. The conformational analysis is a relationship between the energy of the title compound and its geometry. It is demonstrated that comparison between the calculated and experimental results provide a very good agreement. The energetic behavior such as the total energy, atomic charges, dipole moment of the title compound in solvent media were examined using the same methods by applying the Onsager and the integral equation formalism polarizable continuum model (IEF-PCM). © 2017 Elsevier B.V.
Keywords: FT-IR and UV–Vis Spectroscopy; NLO and NPA Analysis; Schiff Base; X-Ray Diffraction